ISOLASI SENYAWA TRITERPENOID DAN UJI ANTIBAKTERI EKSTRAK n-HEKSAN DAUN KAYU ARA (Ficus aurata (Miq.) Miq) - Santoni, Adlis; Efdi, Mai; Bumali, Restu (Jurnal Riset Kimia, 2019)
Triterpenoid isolation from n-hexane extract of kayu ara leaves (Ficus aurata (Miq.) Miq) has been performed. The Isolation has been done by column chromatography method using silica gel as a stationary phase and n-hexane and ethyl acetate as mobile phase with isocratic method and it is continued by trituration method. Isolated compound has white amorphous shape, decomposed at 86-87ÂºC and gives single spot with reddish brown violet in LB reagent and in H2SO4 reagent on TLC test. UV spectra indicate the presence of double bonds in the isolated compound at 204 nm Î»max and IR spectra showed -OH functional group at 3290 cm-1, -CH stretching at 2912,90 cm-1, C=C at 1676 cm-1, C-O stretching at 1054,93 cm-1, and at 1374 cm-1 is spectra of geminal dimethyl compound that are characteristic of triterpenoids which supports ultraviolet spectroscopic data. Antibacterial activity test showed that isolated compound is active in inhibiting the growth of gram-positive bacteria Staphyloccocus aureus and gram-negative bacteria Escherichia coli.